The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/s0004-2803.202100000-54
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Ghrelin Levels and Susceptibility to Colorectal Câncer

Abstract: BACKGROUND AND OBJECTIVE: Considering the association between colorectal cancer (CRC) and both insulin resistance and obesity, and the prominent role of ghrelin in these metabolic disorders, we explored whether plasma levels of ghrelin were associated with CRC. Moreover, in the patients with CRC the possible correlations between ghrelin and insulin, insulin resistance, and body mass index (BMI) as an indicator of obesity were examined. METHODS: A total of 170 subjects, including 82 cases with CRC and 88 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Correspondingly, in vivo experiments with intestinal carcinogenesis mouse models have demonstrated that ghrelin might decrease the occurrence of inflammation-related colon cancer [104]. Recent research further highlights a correlation between low plasma ghrelin levels, obesity, insulin resistance, and increased vulnerability to colon cancer [105].…”
Section: Ghrelin and Colorectal Cancermentioning
confidence: 99%
“…Correspondingly, in vivo experiments with intestinal carcinogenesis mouse models have demonstrated that ghrelin might decrease the occurrence of inflammation-related colon cancer [104]. Recent research further highlights a correlation between low plasma ghrelin levels, obesity, insulin resistance, and increased vulnerability to colon cancer [105].…”
Section: Ghrelin and Colorectal Cancermentioning
confidence: 99%
“…After about twelve to fourteen hours overnight fasting of 170 subjects, the blood samples were obtained in EDTA (anticoagulant), inside microtubes. The samples at 4°C were centrifuged and immediately the plasma was separated and kept at -80°C (24). The plasma level in form of unit of ng/ml of insulin and adiponectin were calculated by Enzyme-linked immunosorbent assay (ELISA) kit (Mercodia, Sweden, and Technique, Finlanl, respectively).…”
Section: Biochemical Assaymentioning
confidence: 99%